1988
DOI: 10.1083/jcb.107.3.1139
|View full text |Cite
|
Sign up to set email alerts
|

Induction of phosphorylation and cell surface redistribution of acetylcholine receptors by phorbol ester and carbamylcholine in cultured chick muscle cells.

Abstract: Abstract. We have investigated the mechanisms regulating the clustering of nicotinic acetylcholine receptor (AChR) on the surface of cultured embryonic chick muscle cells. Treatment of these cells with the phorbol ester 12-0-tetradecanoylphorbol-13-acetate (TPA), a potent activator of protein kinase C, was found to cause a rapid dispersal of AChR clusters, as monitored by fluorescence microscopy of cells labeled with tetramethylrhodamine-conjugated tz-bungarotoxin. The loss of AChR clusters was not accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 58 publications
(78 reference statements)
2
46
0
2
Order By: Relevance
“…Our data obtained with activators of PKA indicate that this kinase is not involved in triggering CD46 downregulation. On the other hand, it has been reported that muscarinic acetylcholine m 1 receptor is downregulated subsequent to its phosphorylation by either PKA (Lee & Fraser, 1993) or by PKC (Ross et al, 1988). Similarly, the CD3~ subunit of the T cell receptor (TCR) is downregulated following its phosphorylation by PKC (Dietrich et al, 1994).…”
Section: Activators Of Neither Protein Kinase C (Pkc) Nor Of Protein mentioning
confidence: 99%
“…Our data obtained with activators of PKA indicate that this kinase is not involved in triggering CD46 downregulation. On the other hand, it has been reported that muscarinic acetylcholine m 1 receptor is downregulated subsequent to its phosphorylation by either PKA (Lee & Fraser, 1993) or by PKC (Ross et al, 1988). Similarly, the CD3~ subunit of the T cell receptor (TCR) is downregulated following its phosphorylation by PKC (Dietrich et al, 1994).…”
Section: Activators Of Neither Protein Kinase C (Pkc) Nor Of Protein mentioning
confidence: 99%
“…Although the phosphorylation events that mediate these effects have not yet been identified, several important molecules in the neuromuscular junction have been demonstrated to be substrates for PKC. PKC phosphorylates the Torpedo nAChR in vitro (Safran et al, 1987), whereas PKC may be directly or indirectly responsible for phosphorylating the nAChR in myotubes (Ross et al, 1988;Miles et al, 1994). Potential PKC phosphorylation sites have been identified on the nAChR ␦ subunit and on the adult skeletal muscle sodium channel ␣ subunit (Miles and Huganir, 1988;Bendahhou et al, 1995).…”
Section: Abstract: Protein Kinase C; Cpkc ␣; Npkc ; Neuromuscular Jumentioning
confidence: 99%
“…Application of phorbol esters, which activate PKC, to myotubes inhibits both basal and acetylcholine receptor inducing activity (ARIA)-stimulated nAChR synthesis (Burstajn et al, 1988;Altiok et al, 1995). Treatment of myotubes with phorbol esters disrupts spontaneously formed nAChR clusters and abolishes the activity of agrin, an nAChR clustering factor (Burstajn et al, 1988;Ross et al, 1988;Wallace et al, 1991), suggesting that PKC may play a role in the distribution of nAChRs in the postsynaptic membrane. The amplitude of currents induced by the iontophoretic application of acetylcholine to chick myotubes and frog endplates is diminished by the activation of PKC (Eusebi et al, 1985;Caratsch et al, 1986).…”
Section: Abstract: Protein Kinase C; Cpkc ␣; Npkc ; Neuromuscular Jumentioning
confidence: 99%
“…Thus, we sought to determine whether ERK1/2 activation is required by Nrg-1 and PMA, two factors known to both induce ERK1/2 activation (Fig. 4A) (15,25) and to inhibit the AChR clustering activity of agrin in myotubes (13,17,18). C2 myotubes were treated for 14 -15 h with either 0.1 nM agrin or 0.1 nM agrin in the presence of 2 nM Nrg-1␤ EGF domain (13), or 50 nM PMA (17).…”
Section: Nrg-1 and Pma Two Known Inhibitors Of Agrin-induced Achr CLmentioning
confidence: 99%
“…Sustained activation of ERK1/2 is a major signaling event induced by Nrg-1 on skeletal muscle cells (15,16). Furthermore, phorbol 12-myristate 13-acetate (PMA), a protein kinase C (PKC) activator that was among the first identified inhibitors of agrin-induced AChR clustering on myotubes (17,18), also induces activation of ERK1/2 in most cells. Here, it was investigated whether agrin can activate ERK1/2 directly and whether such activation can modulate agrin-induced AChR clustering.…”
mentioning
confidence: 99%